European Asylum Policy and its Reforms from a Central and Eastern European Perspective - Töttős, Ágnes (The Policies of the European Union from a Central European Perspective, 2022)
This chapter explores the recent developments of the EU’s asylum policy and focuses in details on three specific issues, namely the short-term actions at EU level given to the 2015 migration crisis, the direction of the long-term reform of the Common European Asylum System, and the most recent developments at the Eastern borders, including the instrumentalization of migration by Belarus and the fleeing of millions from Ukraine. Given the geographical position of Central European countries in the EU, they have been exposed to migratory challenges earlier and to a greater extent than many other parts of the Union. Because of their unique historical and societal context, their reaction is focused on the provision of security instead of allowing for the misuse of the asylum system. Therefore, the three specific issues are introduced with special attention to the effect on and the position of Central Europe and especially the Visegrad countries.Keywords: Common European Asylum System, relocation, asylum reforms, instrumentalization of migration, Ukrainian refugees